A New Method for Generating Traveling-Wave Solutions of Coupled Nonlinear Equations - Jiuli Yin; Shanyu Ding; Lixin Tian; Xinghua Fan (Український математичний журнал, 2012)
We propose a new method of algebraic transformations aimed at finding the traveling-wave solutions of complicated nonlinear wave equations on the basis of simpler equations. The generalized Dullin–Gottwald–Holm (DGH) equation and mKdV equations are chosen to illustrate our method. The solutions of the DGH equation can be obtained directly from the solutions of the mKdV equation. The conditions of appearance of different solutions are also presented. Various types of traveling-wave solutions are obtained for the generalized DGH equation, including periodic solutions, smooth solutions with decay, solitary solutions, and kink solutions. Побудовано новий метод алгебраїчних перетворень для знаходження розв’язків типу біжучих хвиль для складних нелінійних хвильових рівнянь на основі більш простих. Для ілюстрації методу використано узагальнене рівняння Далліна – Готвальда – Холма та модифіковане рівняння Кортевега – де Фріза. Розв’язки рівняння Далліна – Готвальда – Холма можна отримати безпосередньо із розв’язків модифікованого рівняння Кортевега – де Фріза. Наведено також умови для отримання різних розв’язків. Отримано чисельні розв’язки типу біжучих хвиль для узагальненого рівняння Далліна – Готвальда – Холма, серед яких періодичні розв’язки, гладкі розв’язки з запізненням, солітонні розв’язки та кінк-розв’язки.